2005
DOI: 10.1038/nature03456
|View full text |Cite
|
Sign up to set email alerts
|

Controlled multiple quantum coherences of nuclear spins in a nanometre-scale device

Abstract: The analytical technique of nuclear magnetic resonance (NMR) is based on coherent quantum mechanical superposition of nuclear spin states. Recently, NMR has received considerable renewed interest in the context of quantum computation and information processing, which require controlled coherent qubit operations. However, standard NMR is not suitable for the implementation of realistic scalable devices, which would require all-electrical control and the means to detect microscopic quantities of coherent nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
225
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(238 citation statements)
references
References 24 publications
11
225
0
1
Order By: Relevance
“…Whilst electron spins are an obvious choice for manipulating information, nuclear spins provide a robust system in which to store spin information for long periods of time 7 . However, whilst a number of optical 8,9 and quantum Hall based techniques 10 exist for reading the state of small ensembles of nuclear spins, until recently there has been no technique for doing so which is compatible with conventional electronic devices, particularly those in silicon. Using pulsed spin resonance, we recently demonstrated the ability to electrically measure the nuclear spin state of phosphorus donors in silicon 11 with a long spin lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst electron spins are an obvious choice for manipulating information, nuclear spins provide a robust system in which to store spin information for long periods of time 7 . However, whilst a number of optical 8,9 and quantum Hall based techniques 10 exist for reading the state of small ensembles of nuclear spins, until recently there has been no technique for doing so which is compatible with conventional electronic devices, particularly those in silicon. Using pulsed spin resonance, we recently demonstrated the ability to electrically measure the nuclear spin state of phosphorus donors in silicon 11 with a long spin lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical detection of nuclear magnetic resonance has been performed on e.g. two-dimensional electron gases, identifying the origin of the Overhauser field [5], and the electrical readout of nuclear spin states has been achieved for this system [6]. In phosphorus-doped silicon, McCamey et al [7] have recently demonstrated the electrical readout of nuclear spins at 8.6 T. While both these studies employ highly polarized spin systems for the readout, we make use of a spin-dependent recombination process via Si/SiO 2 interface states [8]; this approach does not rely on a polarization of the electron spin system and thus works under experimental conditions where the thermal energy is much larger than the electron Zeeman splitting [9].…”
mentioning
confidence: 99%
“…4, in confirmation of the earlier theoretical calculations [28], manifests the effect of the strong influence of the nonresonant processes on leakage. A second experiment supporting strong nonresonant leakage at short times has been recently made on semiconductor NMR devices by Yusa et al [30] where offresonant multiple quantum coherence effects between levels separated by more than one quantum of nuclear spin quantum number were observed. This experiment is the four level version of the quantum dot experiment by Zrenner et al done with stable nuclei with total spin 3 2 in which the short time multilevel dynamics can be probed.…”
Section: Leakage Effectsmentioning
confidence: 99%